THE COSTS SYSTEMS IN THE INDUSTRIAL TUNA COMPANIES OF MANTA - Govea Andrade, Karina (2017)
The investigation allowed to characterize the companies of the industrial tuna sector of the city of Manta-Ecuador that have established a system of accounting of costs for its management. On the other hand, evaluating the relationship between the degree of use of cost systems on the profitability of companies. Based on these objectives, a descriptive and inferential analysis was made on the relationship between the variables of 15 of the 23 companies involved in the sector of the city of Manta. Thus, it was concluded that there is a significant statistical equality between the use of the system of cost per order of production and the standard cost system to determine profitability. In addition, it was verified that the most used method by the companies is the system of costs by orders of production, identifying that the greater use of the systems is to establish costs to have control, 80% of the companies surveyed have a capital structure mainly family.